Calcium-Sensing Receptor in Breast Physiology and Cancer - Kim, Wonnam; Wysolmerski, John J. (Frontiers in Physiology, 2016)
The calcium-sensing receptor (CaSR) is expressed in normal breast epithelial cells and in breast cancer cells. During lactation, activation of the CaSR in mammary epithelial cells increases calcium transport into milk and inhibits parathyroid hormone-related protein (PTHrP) secretion into milk and into the circulation. The ability to sense changes in extracellular calcium allows the lactating breast to actively participate in the regulation of systemic calcium and bone metabolism, and to coordinate calcium usage with calcium availability during milk production. Interestingly, as compared to normal breast cells, in breast cancer cells, the regulation of PTHrP secretion by the CaSR becomes rewired due to a switch in its G-protein usage such that activation of the CaSR increases instead of decreases PTHrP production. In normal cells the CaSR couples to Gi to inhibit cAMP and PTHrP production, whereas in breast cancer cells, it couples to Gs to stimulate cAMP and PTHrP production. Activation of the CaSR on breast cancer cells regulates breast cancer cell proliferation, death and migration, in part, by stimulating PTHrP production. In this article, we discuss the biology of the CaSR in the normal breast and in breast cancer, and review recent findings suggesting that the CaSR activates a nuclear pathway of PTHrP action that stimulates cellular proliferation and inhibits cell death, helping cancer cells adapt to elevated extracellular calcium levels. Understanding the diverse actions mediated by the CaSR may help us better understand lactation physiology, breast cancer progression and osteolytic bone metastases.